PENINGKATAN KETERAMPILAN MENULIS TEKS EKSPLANASI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE, INTEGRATED, READING AND COMPOSITION (CIRC) SISWA KELAS VII.1 MTS. MUHAMMADIYAH TALLO KOTA MAKASSAR - Ira Afrianti; M. Agus; Wahyu Ningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve the writing skills of explanatory texts of class VII.1students at MTs. Muhammadiyah Tallo, Makassar City, through the application ofthe Cooperative, Integrated, Reading, and Composition (CIRC) learning model.This study focuses on the main question: " How can the CIRC model improvestudents writing skills?''.The methodology used is a classroom action research(CAR) design with a qualitative and quantitative approach to collect relevant data.The study was conducted in two cycles, where each cycle consisted of fourstages: planning, implementation, observation, and reflection. Learning activitiesincluded group discussions, reading explanatory texts together, and writingexercises with feedback from teachers to improve students understanding. Theresults of this study showed a significant increase in students writing skills. In thefirst cycle, the average student score showed progress, but many still had difficultyin composing coherent texts. After the implementation of the CIRC model andimprovements made in the second cycle, the percentage of student completionincreased to 87%, with some students achieving the highest score of 95. Thisimprovement can be seen in several aspects, namely first, the content of the textwhere students are able to convey more comprehensive and systematicinformation in writing explanatory texts, and can identify general statements andrelevant explanations. Second, the organization of the text, where the structure ofthe explanatory text becomes more orderly and clear, following a logical sequencefrom beginning to end. Third, the use of language, where students show anincrease in the use of appropriate and contextual vocabulary, and write sentenceswith a more varied structure. Fourth, writing mechanics that show reduced errors,indicating a better understanding of effective writing.